1995
DOI: 10.1016/0035-9203(95)90656-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunodiagnostic studies on Onchocerca volvulus and Mansonella perstans infections using a recombinant 33 kDa O. volvulus protein (Ov33)

Abstract: A total detergent-soluble extract of adult female Onchocerca volvulus (OvAg) and a recombinant O. volvulus protein (Ov33) linked to glutathione-S-transferase (GST) were compared with regard to their serodiagnostic suitability for differentiating between O. volvulus and Mansonella perstans infections in a region endemic for both filarial worms in western Uganda. Using OvAg in an enzyme-linked immunosorbent assay (ELISA), 98.8% sensitivity was obtained examining 84 O. volvulus microfilariae (mf) carriers living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The 100% sensitivity of our test recorded in four of the five geographic regions tested is an improvement of previous results, 9,[11][12][13]19,26,27 and shows that the combination of both immunodiagnostic antigens into one hybrid protein had a cumulative effect. Currently, we do not have an explanation for the lack of seroreactivity of two Ecuadorian onchocerciasis sera with OvH2 or OvH3.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The 100% sensitivity of our test recorded in four of the five geographic regions tested is an improvement of previous results, 9,[11][12][13]19,26,27 and shows that the combination of both immunodiagnostic antigens into one hybrid protein had a cumulative effect. Currently, we do not have an explanation for the lack of seroreactivity of two Ecuadorian onchocerciasis sera with OvH2 or OvH3.…”
Section: Discussionsupporting
confidence: 63%
“…This is supported by previous data that demonstrated that Ov33 is recognized by sera from patients with onchocerciasis before the onset of patency. 26 Early seroconversion is conceivable, since both Ov20 and Ov33 are expressed by infective larvae of O. volvulus, 8,14 which makes the hybrid protein a sensitive tool to monitor exposure to O. volvulus. The potential of OvH2 for diagnosing exposure to O. volvulus transmission as well as early and light infections, might be particularly valuable, i.e., in situations where it is difficult to diagnose onchocerciasis by detection of microfilariae or microfilarial DNA, e.g., in situations after interruption of transmission and/or following prolonged treatment with ivermectin.…”
Section: Discussionmentioning
confidence: 99%
“…Brown et al (1970) observed M. perstans mff during health surveys in primary schools in Uganda, and a review by Hawking (1977) stated that 40%-50% of inpatients at the main referral hospital in Kampala had M. perstans mff in their blood. More recently, attention has been drawn to this infection in Uganda as the result of the activities of the national onchocerciasiscontrol programme (Tawill et al, 1995;Fischer et al, 1996).…”
mentioning
confidence: 99%
“…1,3 Cross-reactions between O. volvulus and Mansonella species impede the differentiation of these parasites by serologic diagnosis using worm extracts. 4 Although isolated microfilariae (mf) of both species can be differentiated morphologically, species differentiation in histologic sections is difficult. Since the mf densities of M. streptocerca are often relatively low, methods other than the standard skin snip technique are required for accurate detection of this species.…”
mentioning
confidence: 99%